2005
DOI: 10.2174/1568005054201553
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Envelope Evolution and Vaccine Efficacy

Abstract: Transmission of human immunodeficiency virus type 1 (HIV-1) selects for envelope variants with a number of defined properties, including use of CCR5 as the preferred coreceptor, binding to CCR5 in a distinct manner compared to HIV-1 isolated later in infection, shorter variable (V) regions, and fewer N-linked glycosylation sites. These features define the ideal target for an envelope-containing vaccine designed to elicit neutralizing antibody. If a candidate vaccine were sufficiently potent to elicit sterilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 80 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…The CD8 cytotoxic T cell response (29,30) and the neutralizing antibody production are largely responsible for the viral control leading into the chronic phase. During the chronic phase, the highest selection pressure due to neutralizing antibodies is on the Env glycoprotein of the virus (31), which undergoes rapid evolution via changes in the pattern of N-glycosylation and charge on the Env glycoprotein (32). Recently, several genetic signatures have been identified that can distinguish viruses from different stages of the disease that include but are not limited to changes in putative N-glycosylation sites (PNGS) (18,(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…The CD8 cytotoxic T cell response (29,30) and the neutralizing antibody production are largely responsible for the viral control leading into the chronic phase. During the chronic phase, the highest selection pressure due to neutralizing antibodies is on the Env glycoprotein of the virus (31), which undergoes rapid evolution via changes in the pattern of N-glycosylation and charge on the Env glycoprotein (32). Recently, several genetic signatures have been identified that can distinguish viruses from different stages of the disease that include but are not limited to changes in putative N-glycosylation sites (PNGS) (18,(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…However, post-translational modified target antigens often contribute to diagnosis of autoimmune diseases like rheumatoid arthritis and systemic lupus erythematosus [15,16]. Post-translational glycosylation of antigens also represents an important target of anti-viral responses against HIV and influenza [17]. …”
Section: Why Is Candidate Biomarker Validation Important?mentioning
confidence: 99%
“…Modification of the glycan shield under immunological pressure seems to afford a mechanism of immunological escape that allows the virus to persist in the presence of an evolving antibody repertoire [19,20]. Apparently there is immunologically mediated selection pressure both to change the position of individual glycans and to conserve the overall glycan shield of Env since mutations are selected that both destroy and create N glycosylation sites.…”
Section: Introductionmentioning
confidence: 99%